2000
DOI: 10.1002/etc.5620190323
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent stimulation of hepatic retinoic acid hydroxylation/oxidation and glucuronidation in brook trout, Salvelinus fontinalis, after exposure to 3,3′,4,4′‐tetrachlorobiphenyl

Abstract: Abstract-Extremely low stores of vitamin A have been reported in fish and birds inhabiting regions contaminated by coplanar polychlorinated biphenyls (PCBs) and other organochlorines, suggesting many possible effects on retinoid biochemical pathways. Metabolic imbalances associated with biologically active retinoids (e.g., retinoic acid) could be associated with teratogenesis, edema, growth inhibition, reproductive impairment, immunosuppression, and susceptibility to cancer. Sexually mature brook trout were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Increases in the circulating vitamin A after exposure to PCBs have already been reported in rats and were linked to a reduction of hepatic retinoid stores (Bank et al, 1989;Zile , 1992), suggesting an enhanced mobilisation of hepatic vitamin A in PCB exposed animals. A reduction of hepatic retinoid stores following PCB exposure has also been observed in fish (Boyer et al, 2000), birds (Bishop et al, 1999;Murk et al, 1994) and aquatic mammals Nyman et al, 2003). Although several in vivo and in vitro studies showed that the activity of different liver enzymes involved in the retinoid metabolism were modified following PCB exposure (Fig.…”
Section: Relationships Between Pcbs Ho-pcbs and Vitamin Amentioning
confidence: 85%
See 1 more Smart Citation
“…Increases in the circulating vitamin A after exposure to PCBs have already been reported in rats and were linked to a reduction of hepatic retinoid stores (Bank et al, 1989;Zile , 1992), suggesting an enhanced mobilisation of hepatic vitamin A in PCB exposed animals. A reduction of hepatic retinoid stores following PCB exposure has also been observed in fish (Boyer et al, 2000), birds (Bishop et al, 1999;Murk et al, 1994) and aquatic mammals Nyman et al, 2003). Although several in vivo and in vitro studies showed that the activity of different liver enzymes involved in the retinoid metabolism were modified following PCB exposure (Fig.…”
Section: Relationships Between Pcbs Ho-pcbs and Vitamin Amentioning
confidence: 85%
“…In the liver, contaminants such as 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), PCBs and pesticides were able to modulate the regulation of some cytochrome P450 (CYP) enzymes that are also involved in the metabolism and the catabolism of retinoic acid (Fig. 1, points 1 and 2) (Boyer et al, 2000, Leiva-Presa et al, 2006Nová k et al, 2008). The activity of enzymes that esterify retinol and hydrolyse retinyl esters such as retinyl ester hydrolase (REH), acyl-CoA:retinol acyltransferase (ARAT) and lecithin:retinol acyltransferase (LRAT) were also shown to be modulated by PCBs and TCDD in fish and laboratory animals ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic oxidative catabolism of RA has been reported in non-mammalian vertebrates classes: fish (Gilbert et al 1995;Boyer et al 2000) and birds (Swindell et al 1999). Whereas the genes associated with RA metabolism clearly evolved long before the appearance of vertebrates (Albalat 2009) and amphibian models are widely used to study RA-related mechanisms in amphibian embryo development (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures to assay the RA conversion to 4-oxo-RA were conducted under yellow incandescent light to prevent spontaneous isomerization of retinoids and according to the method of Boyer et al (2000), with slight modifications. A stock solution of 3.0 mM atRA or 13cisRA in methanol 100 % was kept at -20°C and checked regularly for purity by comparing spectrometer and HPLC chromatograms.…”
Section: Enzymatic Assays and Hplc Analysis Of The Reaction Productsmentioning
confidence: 99%